2018
DOI: 10.1007/s11079-018-9492-1
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Islamic Vs. Conventional Banks: Evidence on the Suitability of the Basel Capital Ratios

Abstract: This paper examines the effect of various types of bank capital on the profitability and efficiency of conventional and Islamic banks. Our results show that higher quality forms of capital improve the profitability and efficiency for both systems although the results are stronger for conventional banks.The capital effect is more pronounced for large, too-big-to-fail, and highly capitalized banks. The results are robust across various subsamples, alternative profitability and efficiency measures, and different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
(83 reference statements)
4
11
0
Order By: Relevance
“…The result of this relationship proves the pecking order theory which suggests a negative relation between profitability and leverage. Furthermore, there was a direct relation found between ROE and leverage, and this relation was also found by Anafo et al (2015); Chisti et al (2013); Rajha and Alslehat (2014); Bitar et al (2016); Pratomo and Ismail (2007); and Akhtar et al (2011).This direct relation validates the presence of trade-off theory which deals with a direct relation between the performance of an organization and debt. In addition to that, EPS showed contradictory results between profitability and leverage.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The result of this relationship proves the pecking order theory which suggests a negative relation between profitability and leverage. Furthermore, there was a direct relation found between ROE and leverage, and this relation was also found by Anafo et al (2015); Chisti et al (2013); Rajha and Alslehat (2014); Bitar et al (2016); Pratomo and Ismail (2007); and Akhtar et al (2011).This direct relation validates the presence of trade-off theory which deals with a direct relation between the performance of an organization and debt. In addition to that, EPS showed contradictory results between profitability and leverage.…”
Section: Discussionsupporting
confidence: 73%
“…The result showed that equity ratio, total asset and financing to total assets had a direct effect on performance. The same positive relationship between leverage and profitability was also identified by Chisti, Ali, and Sangmi (2013); Bitar, Hassan, Pukthuanthong, and Walker (2016); Pratomo and Ismail (2007); and Akhtar, Ali, and Sadaqat (2011).…”
Section: Trade-off Theorysupporting
confidence: 65%
See 1 more Smart Citation
“…Moreover, several studies have emphasised that there is a lack of a well-defined and adequate regulatory and supervisory framework to govern Islamic banks in accordance with Shari'ah (Hassan et al, 2017). There is clearly a large body of literature on the role of regulations in the performance and efficiency of Islamic banks (Alam, 2013;Bitar et al, 2018;Mohd Noor et al, 2020;Wan Ibrahim & Ismail, 2020), but there are literature focusses on the margins of Islamic banks. For instance, Alam (2013) conducted a study on the relationship between banking regulations and the efficiency and risk-taking behaviour of Islamic banks.…”
Section: Introduction 11 Backgroundmentioning
confidence: 99%
“…For instance, Alam (2013) conducted a study on the relationship between banking regulations and the efficiency and risk-taking behaviour of Islamic banks. Bitar et al (2018) examined the role of the Basel III regulatory framework on the efficiency of Islamic and conventional banks, finding a negative relationship between the capital requirements proposed and Islamic bank efficiency. This implies that greater capital requirements would impede the effectiveness of the banking system.…”
Section: Introduction 11 Backgroundmentioning
confidence: 99%